Abundant natural resources in the growth process : an advantage or disadvantage for a region? - Lundgren, Nils-Gustav (Luleå tekniska universitet, Samhällsvetenskap, 2006)
The northern parts of Norway, Sweden, Finland and North West Russia, now days referred to as the Barents region, have undergone dramatic political, social and economic changes since the end of the 19th century. During the last 120 years the region's natural resources have been exploited industrially on a scale and with an intensity never seen before in history. The world market demand for raw materials increased dramatically in the late 19th century, whilst at the same time scarcity, increasing prices and even exhaustion of sources of raw materials affected some of the early industrialised centres of western and southern Europe. As a result there were an inflow of entrepreneurs and capital from outside to different parts of the Barents region becoming an important part in the industrial exploitation of the regions forests, mineral deposits and in hydro power plant building. The aim of the paper is to discuss to what extent abundant natural resources was an advantage or perhaps a disadvantage for the economic growth process of the Barents region. Different approaches on that topic has been emphasised in the public arena and in academic research during different time periods and will be summarised and critically discussed in the paper. Godkänd; 2006; 20070919 (ysko)